THE EFFECT OF USING ROLE-PLAY METHOD IN IMPROVING SPEAKING SKILLS OF BASIC LEVEL STUDENTS AT CENTRAL COURSE - Sarifudin Sarifudin; Wawan Herry Setyawan (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
This article examines the impact of employing the Role-Play method in improving the speaking skills of basic-level English learners in the Central English Course. Speaking a foreign language often presents challenges, particularly for beginner students who lack confidence and opportunities for practical application. Role-play, an interactive teaching strategy, fosters real-world communication by creating scenario-based learning environments, enabling students to engage in language use actively. A quantitative approach was adopted to assess the effectiveness of the Role-Play method. The research involved two groups: an experimental group participated in role-play activities and a control group followed traditional teaching methods. In this study, quantitative data were collected through pre-test and post-test assessments to measure the effectiveness of the Role-Play method in improving students' learning progress in fluency, accuracy, and confidence. This approach enabled precise statistical calculations and pattern identification, providing valuable insights into the impact of the intervention. The findings indicate that the Role-Play method significantly enhances language acquisition, with the experimental group demonstrating greater improvements in EFL students’ speaking skills than the control group. This study underscores the value of integrating interactive and practical approaches into EFL classrooms. Role-play is a useful tool to connect classroom learning with authentic communication experiences, allowing students to apply theoretical knowledge in meaningful, real-world contexts. This research provides valuable insights into innovative pedagogical methods for foreign language learning.